Liquid Levothyroxine Formulation Taken during Lunch in Italy: A Case Report and Review of the Literature - Carlo Cappelli; Ilenia Pirola; Maurizio Castellano (Case Reports in Endocrinology)
Levothyroxine (L-T4) is among the most widely prescribed medications in the world, and it is considered by the World Health Organization an essential medicine for basic health care. Replacement therapy has always been considered straightforward although different factors may interfere with intestinal absorption of L-T4, including food, dietary fibre, coffee, drugs, and gastrointestinal diseases. For these reasons, current guidelines recommend that L-T4 should be taken in a fasting state because its absorption is maximised when it is taken on an empty stomach, reflecting the importance of gastric acidity in the absorption process. In addition to sodium L-T4 in tablet form, various formulations (soft-gel capsules and liquid solutions) have become available for clinical use in the last years promising improved absorption. We described a 31-year-old Italian man who took liquid levothyroxine formulation during lunch. He was under replacement therapy with liquid levothyroxine 75 mcg daily for hypothyroidism due to Hashimoto thyroiditis for three years. During confirmation of the L-T4 replacement therapy, the patient stated that he was going to continue to “take liquid levothyroxine during (his) lunch every day.” We recommended taking the medication correctly in the morning at least thirty minutes before breakfast and repeating TSH, fT4, and fT3 after three months. The thyroid hormonal profiles taken after 3 and 6 months were comparable to those when the patient was taking the medication during lunch. In conclusion, liquid levothyroxine formulation should be preferred in case of malabsorption or potential malabsorption. Liquid formulation should be preferred due to the possibility of taking it during breakfast, which significantly improves the compliance of patients. Further studies are needed to evaluate the possibility of taking liquid L-T4 during lunch.